Complexity in the sciences of the Internet and its relation to communication sciences. Issue 1 (1st June 2019) - Gonzalez, Wenceslao J.; Arrojo, Maria Jose
The structural and dynamic dimensions of complexity of the Internet are connected with epistemological and ontological factors, which are the main modes of complexity of the sciences of the Internet. These dimensions and modes of complexity are relevant for the communication sciences, because this field is one of the most important areas of development of this network of networks. Philosophy needs to address the problems of complexity that arise from the sciences of the Internet that have consequences for the communication sciences. This article deals with these problems through a new approach in the philosophy of communication sciences based on the sciences of the artificial conceived as sciences of design.